(untitled) (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2024)
Agriculture is central to Tanzania's rural economy, but its underperformance drives many households in Sumbawanga Rural District to seek non-farm activities to combat poverty. This study investigates the impact of such activities on poverty reduction. It identifies drivers pushing farmers towards non-agricultural work, like low farm earnings and land scarcity, and explores how these activities affect household income. Data from 195 farming households reveals non-farm activities contribute significantly to income, ranging from 43% to 50%. Despite Tanzania's decreasing poverty rate (25.7%) in 2020, around 26 million still live in extreme poverty. The study suggests promoting non-agricultural endeavours like carpentry and animal husbandry to diversify income sources and alleviate poverty. Overall, it highlights the importance of non-farm activities in rural prosperity and recommends their integration into poverty reduction strategies.